Effect of role ambiguity and psychological safety on employees' innovative work behavior intention - Hadini Kusuma, Aflaha; Etikariena, Arum (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2023)
The organization environment has low role ambiguity and high psychological safety so innovation can be an organizational advantage. This research used a quasi-experimental study using the Experiment Vignette Method (EVM), which aims to measure the effect of role ambiguity and psychological safety on employees' innovative work behaviour intention. The research instrument used a questionnaire distributed using Google Forms. Data collection was carried out using a purposive sampling method and obtained 262 marketplace employees in Indonesia. Independent manipulation variables were arranged as 4x2 comic strips with 4 variations of scenarios as well as measuring employee innovative work behaviour intentions using an innovative work behaviour intention questionnaire. Two-way ANOVA analysis shows that there is a significant effect of role ambiguity on employees' innovative work behaviour intention. In addition, employees with high psychological safety also show more intention to behave innovatively. This study also shows that there is an interaction effect between role ambiguity and psychological safety on employee innovative work behaviour intention.